Diabetes and bacterial co-infection are two independent risk factors for respiratory syncytial virus disease severity - Sivgin, Hakan; Cetin, Sirin; Ulgen, Ayse; Li, Wentian (Frontiers in Medicine, 2023)
Diabetes mellitus (DM) is common among older adults hospitalized with lower respiratory tract infection, yet the information on impact of DM on disease severity is limited. We analyzed retrospectively forty-six Turkish patients infected with respiratory syncytial virus (RSV), with information on their comorbidities, co-infection status, and symptoms. Patients are grouped into four severity levels from mild to most severe, according to lung parenchymal infiltrations status and oxygen level. Similar to previous published studies, we found comorbidities of diabetes, heart failure, hypertension, co-infection of any types and bacterial co-infection, and age, are associated with the disease severity. Cough is the most common symptom (89%), followed by fever (26%), and myalgia, dyspnea, and weakness (around 20%). By a second-order analysis (two-variable regression), we identified two independent risks for disease severity, first is represented by diabetes, and second represented by bacterial co-infection. We observed two patients whose most more severe symptoms were not associated with an old age, but associated with a combination of diabetes and bacterial co-infection. To confirm the true causality from the statistical correlation, further studies are needed.